“DALSTON! WHO ASKED U?”: A Knowledge-Centred Perspective on the Mapping of Socio-Spatial Relations in East London - Jungfer, Carsten; Palmieri, Fernanda; Kling, Norbert (Urban planning, 2022)
Since the turn of the millennium, Dalston in the London Borough of Hackney has experienced fundamental change through public and private investment in new infrastructure and processes of urban restructuring. This was paralleled by the reform of the national planning system, which aimed to devolve decision-making to the local level and increase the possibilities for residents and stakeholders to participate in planning processes. However, the difficulty of translating local needs and aspirations into policy goals and broadly accepted area action plans resulted in a crisis, which, in 2018, led to the introduction of the Dalston Conversation and subsequently the revision of planning goals. It is in this context that the Relational States of Dalston mapping project generated and assembled local knowledge about the web of socio-spatial relations between different local actors and in this way highlighted the significance and fragility of the communities’ networks and their spatial dimensions. The collection, ordering, integration, and production of knowledge can be seen as part of the core work in urban planning processes and policymaking. Which forms of knowledge are routinely used in planning contexts and define the relationship between planning action and urban transformation? To what extent could the mapping of local community relations add to this knowledge and help to improve decision-making processes in contested spaces of knowledge? In what ways could a relational understanding of space and architectural modes of research and representation contribute to the analysis, conceptualisation, and communication of local community relations? This article engages with these questions, using the mapping project in Dalston as a case study.